2016
DOI: 10.1177/0163278716644954
|View full text |Cite
|
Sign up to set email alerts
|

Rasch Analysis and Differential Item Functioning of a Social Support Measure in Jail Inmates With HIV Infection

Abstract: The protective effects of social support on health have been documented in a variety of groups. For HIV-infected persons released from correctional settings, strong social support may be particularly important for obtaining effective postrelease medical treatment and supportive services. Researchers and program evaluators seeking to improve access and adherence to postrelease HIV medical care in this population need accurate measures for the level and type of social support, but current measures have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 82 publications
0
19
0
2
Order By: Relevance
“…56 In terms of perceived social status, the odds of some medical conditions have been documented to be upwards of 3.7-fold when comparing the bottom rung of the social ladder to the higher rungs. 58,59 In order to account for this, we dichotomized our social support measure using a median split, an approach employed by others who have used the CLSA data. Social class is a complex phenomenon sometimes captured via the use of indicators which measure either subjective social status or SE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…56 In terms of perceived social status, the odds of some medical conditions have been documented to be upwards of 3.7-fold when comparing the bottom rung of the social ladder to the higher rungs. 58,59 In order to account for this, we dichotomized our social support measure using a median split, an approach employed by others who have used the CLSA data. Social class is a complex phenomenon sometimes captured via the use of indicators which measure either subjective social status or SE.…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence of a ceiling effect for our social support indicator, with a build up of scores at the upper, more positive end of the instrument, which has also been observed in other populations using the same measure. 58,59 In order to account for this, we dichotomized our social support measure using a median split, an approach employed by others who have used the CLSA data. 32 We found that the likelihood of migraine prevalence was often reduced for women who engaged in most forms of physical activity (ie, walking, light, moderate, strenuous sports, or muscle strengthening).…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, los investigadores examinaron el contenido de dichos ítems desde aspectos teóricos del apoyo social y consideraron que, además de que estos sí pertenecen al constructo de apoyo social, no sería ventajoso dividir el instrumento en dos conjuntos de ítems siendo uno de ellos compuesto por solo tres preguntas. Por lo anteriormente expuesto, fue inferido que el cuestionario MOS-SSS es unidimensional, tal como se demostró en otros estudios donde este instrumento fue evaluado utilizando el modelo de Rasch (41)(42).…”
Section: Discussionunclassified
“…Como ha sido publicado en otros estudios (41)(42), en el mapa de Wright fue observado que los ítems se localizan justo hacia el centro del mapa. También se observó un importante número de personas sin ítems alineados.…”
Section: Discussionunclassified
“…However, inmates often lose their support from their families due to a long history of drug abuse and involvement in crime (Lichtenstein et al, 2002). Family social support plays a significant role to deal with QoL (Kim et al, 2017). Social support can be gained from family, friends, and significant others ( In addition, the prison climate is an underlying terminology, which embraces social, emotional, organizational, and physical characteristics of a rehabilitative institution perceived by inmates and staff (Ross et al, 2008).…”
Section: Development Of Research Modelmentioning
confidence: 99%